Allogeneic hematopoietic stem cell transplantation with the modified myeloablative conditioning regimen for children with chronic active Epstein–Barr virus infection. Issue 4 (15th November 2022) - Luo, Yanhui; Wei, Ang; Wang, Bin; Zhu, Guanghua; Zhang, Rui; Jia, Chenguang; Yan, Yan; Zhou, Xuan; Yang, Jun; Qin, Maoquan; Wang, Tianyou
ABSTRACT: Importance: Allogeneic hematopoietic stem cell transplantation (allo‐HSCT) is considered the only effective treatment for chronic active Epstein–Barr virus infection (CAEBV). The clinical efficacy and safety of allo‐HSCT with different conditioning regimens in children with CAEBV remain unclear. Objective: To evaluate the effectiveness and safety of allo‐HSCT with the modified myeloablative conditioning (MAC) regimen for children with CAEBV and also the factors affecting the outcomes. Methods: We retrospectively analyzed children with CAEBV who underwent allo‐HSCT with the modified MAC regimen at Beijing Children's Hospital, Capital Medical University from October 2016 to June 2021. Data related to the clinical manifestations, engraftment, and outcome were extracted from the medical records. Results: The cohort comprised 41 patients (24 males, 17 females) with a median transplantation age of 92.6 (60.4, 120.7) months and a median follow‐up time of 28.2 (15.3, 40.2) months. Four patients (9.8%) died, among which three died from primary disease relapse, and one died from grade IV acute graft‐versus‐host diseases (aGVHD) after stopping treatment. The 3‐year overall survival (OS) and 3‐year event‐free survival (EFS) rates were 88.8% ± 5.4% and 85.0% ± 5.7%, respectively. The 3‐year OS and EFS did not significantly differ between the patients with hemophagocytic lymphohistiocytosis (HLH) and the patient without HLH (87.7% ± 6.8% vs . 91.7% ± 8.0%, P = 0.790; 85.0% ± 6.9% vs . 84.6% ± 10.0%, P = 0.921), or among the patients with complete remission, partial remission, and activity disease before HSCT (all P > 0.05). Multivariate analysis showed that grade III–IV aGVHD was a risk factor for mortality (Hazards ratio: 11.65, 95% confidence interval: 1.00, 136.06; P = 0.050). Interpretation: Allo‐HSCT with the modified MAC regimen is safe and effective for pediatric CAEBV. This treatment benefits patients with HLH or active disease. Patients with Grade III–IV aGVHD may be associated with worse outcomes. Abstract : Allogeneic hematopoietic stem cell transplantation (allo‐HSCT) with the modified myeloablative conditioning (MAC) regimen is safe and effective for pediatric chronic active Epstein–Barr virus. The 3‐year overall survival (OS) and 3‐year event‐free survival (EFS) rates were 88.8% ± 5.4% and 85.0% ± 5.7%, respectively. The 3‐year OS and EFS did not significantly differ between the hemophagocytic lymphohistiocytosis (HLH) and non‐HLH groups, or among the complete remission, partial remission, and activity disease groups. Patients with concomitant HLH and patients with the active disease before allo‐HSCT also benefit from modified MAC‐HSCT. Patients with grade III–IV acute graft‐versus‐host diseases (aGVHD) had lower 3‐year OS and EFS rates than those without aGVHD or with grade I–II aGVHD.